Detailed Fruit Anatomy of the Genus Grammosciadium DC. (Apiaceae) - Karakaya, Muhammet Ali; Mavi İdman, Özlem; Bani, Barış (SDU Journal of Natural and Applied Sciences, 2021)
The genus Grammosciadium is a member of the family Apiaceae and has four taxa namely G. daucoides, G. macrodon subsp. macrodon, G. macrodon subsp. nezaketiae and G. cornutum distributed in Turkey. Because the fruit anatomical characters are distinctly important for the taxonomy of the family Apiaceae, this study includes the detailed anatomy of the fruits of the genus. Moreover, some measurements from the fruit anatomy are given. Besides the general anatomy of them, the taxa are evaluated by both qualitative characters such as mericarp types and clarity of ribs and quantitative characters such as number of vascular bundles, number of vittae, size of mericarp, vittae, endosperm and vascular bundles. All the data presented in this research study may be used as a basis for all possible research on the taxonomy of the family and the genu.
Keywords: 15. Life on land